“Turn-On” Protein Fluorescence: In Situ Formation of Cyanine Dyes - Yapici, Ipek (J Am Chem Soc, 2014)
[Image: see text] Protein reengineering of cellular retinoic acid binding protein II (CRABPII) has yielded a genetically addressable system, capable of binding a profluorophoric chromophore that results in fluorescent protein/chromophore complexes. These complexes exhibit far-red emission, with high quantum efficiencies and brightness and also exhibit excellent pH stability spanning the range of 2–11. In the course of this study, it became evident that single mutations of L121E and R59W were most effective in improving the fluorescent characteristics of CRABPII mutants as well as the kinetics of complex formation. The readily crystallizable nature of these proteins was invaluable to provide clues for the observed spectroscopic behavior that results from single mutation of key residues.